Anak Jalanan di Kota Medan - Putra, M. Harwansyah; Siregar, Afnita Marni; Ritonga, Dahniar; Linri, Linri; Rambe, Nurul Zanna (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Street children are essentially victims and phenomena that arise as a side effect of mistakes or inaccuracies in the selection of a development model that has so far placed too much emphasis on growth aspects and regional development bias which has been too concentrated in big cities. The city of Medan, like other big cities in Indonesia, faces the problem of many street children. According to the Raperda for Child Protection, the Medan Government that the number of street children in 2022 will reach 550 souls. Seeing the increasing number of street children in the city of Medan and the many factors that cause them to become street children, the purpose of this research is to find out the background of street children choosing to work on the streets, the social relations of street children and the physical health of street children. The method used is descriptive research, quantitative meaning this research describes a situation according to events as they are that can be interviewed, observed and studied documentation. Quantitative descriptive method is defined as a research method in the form of a description with numbers. From several locations in Medan City that were used as places for children to make money in this study, there were three points used as research locations, namely Pasar Raya MMTC, Terminal Aksara and Alfamidi in Medan City. The results showed that poverty, parental encouragement, social environment, low education and wanting to have their own money were the factors behind street children in Medan City. By working as street children, the social relations of street children are closed, they don't care, and they are lazy. The physical health of street children, which the researchers have observed, is that most of the street children experience skin irritation and thin bodies due to unhealthy eating patterns. Keywords: Street Children, Causative Factors, Social Relations, Physical Health